Answer:
x = 1
y = 2
Step-by-step explanation:
y =8x - 6 ---------------------------------(I)
y = 2x -------------------------------------(II)
substitute y = 2x in equation (I)
2x = 8x - 6
Add 6 to both sides
2x + 6 = 8x
Subtract 2x from both sides
6 = 8x - 2x
6 = 6x
Divide both sides by 6
6/6 = x
x = 1
Substitute x = 1 in equation (II)
y = 2*1
y = 2
Answer: 76
Step-by-step explanation: i just know
Answer:
a +b = 2
Step-by-step explanation:
a +3 = 6
a = 6 -3
a = 3
Plugin a =3 in the equation,
a*b +5*a +3*b + 15 = 24
3b + 5*3 + 3b + 15 = 24
3b + 15 + 3b + 15 = 24 {combine like terms}
3b + 3b + 15 + 15 = 24
6b + 30 = 24 {Subtract 30 from both sides}
6b = 24 -30
6b = -6 {divide both sides by 6}
b = -6/6
b = -1
a + b = 3 + ( -1)
= 2
2 over 45 just so that you know
Answer:
which principle prevents a brach from abusing its power
Step-by-step explanation: